Cross Return Predictability in Pacific Basin Stock Markets - Chan, Wai-Sum (Institutional Knowledge at Singapore Management University, 1994)
The return transmission across the stock markets of the Pacific Basin is examined. Using the multiple time-series approach, the analysis identifies explicitly the interaction among national markets and investigates the predictability of return on a post-sample basis. The analysis covers the period before and after the October 1987 crash. The in-sample estimation results show that the markets do not generally follow random walk. There are multivariate return transmission structures, and incorporating these structures can reduce the residual standard error and improve the fit of the models. In-sample model fitting, however, does not necessarily imply better forecast performance. On the post-sample prediction basis, there is no evidence that using only a country's own past returns can outperform the simple forecast using the historical mean. Incorporating other countries' past returns, however, can improve the forecast performance.